Recent advances in tough and self-healing nanocomposite hydrogels for shape morphing and soft actuators. (5th February 2020) - Cheng, Feng-mei; Chen, Hong-xu; Li, Hai-dong
Graphical abstract: Highlights: Colloid-crosslinked hydrogels with outstanding strength and toughness have emerged. Colloids with different geometries and properties serve as energy dissipation centers. Responsiveness to external stimuli has been obtained by using functional monomers. Smart hydrogel devices are fabricated and undergo shape morphing and actuation. Abstract: This review article accounts most recent progresses on tough, stretchable and self-healing nanocomposite hydrogels and potential applications. Nanoparticles including silica spheres, clay nanorods, nanotubes, nanosheets, and graphene and derivatives have been used to adsorb or chemically bond polymer chains into three-dimension networks. Reversible detachment of polymer chains from nanoparticles not only entitles stretchability and toughness, but also makes the hydrogels self-healable and recoverable. Moreover, soft and flexible micelles of surfactants and block copolymers are used as macro-crosslinkers and centers for energy dissipation. The hydrophobic association within the micelle cores is critical for the improved mechanical properties of the hydrogels. The nanocomposite structures are combined with other non-covalent interactions including supramolecular recognition, metal ion coordination and hydrogen bonding to further mediate the mechanical properties and functionalities of the hydrogels. Applications of multiresponsive nanocomposite hydrogels for shape morphing materials and soft actuators are discussed.